Impact of Oil Price Shocks on the Macroeconomy: Evidence from Nigeria. (2014)
The role of oil price shocks in the movements of key macroeconomic fundamentals such as output and inflation has been the focal point of many empirical enquiries. However, earlier studies on the oil price- output-inflation relationship in Nigeria hardly took an explicit account of potential non-linearities. This study, therefore, investigated the impact of oil price shocks on output and inflation in Nigeria between 1970 and 2006. A macroeconometric model which captured both the direct and indirect relationships between oil price shocks, output and inflation, was employed. Three alternative measures of oil price shocks namely linear, asymmetric and volatility were considered. The behavioural equations were estimated using the three-stage-least-squares technique and a general-to specific procedure was used to minimise the loss of valuable information. The linear benchmark model showed that the effect of oil price shocks on inflation was moderately important, while the effect on output was not significant. Specifically, in response to a doubling of oil price, output rose by 0.20% and it resulted in a 0.25% decline in inflation. The results of the asymmetric model indicated that a 100% increase in oil price would cause output to rise by 0.57%, but it would decline by only 0.13% following an oil price reduction of the same order of magnitude. The volatility measure showed that doubling the oil price would raise output by 0.45% and inflation would increase by 0.15%. The estimated results suggested that oil price shocks had trifling impact on output, while it appeared to have slight effect on inflation. This implied that the enclave nature of the oil sector and its weak linkages with the rest of the economy as well as better management via sterilisation may have moderated the effect of oil price shocks on both output and inflation respectively.